Correction: Fabrication of a uniaxial cellulose nanocrystal thin film for coassembly of single-walled carbon nanotubes. Issue 55 (19th May 2016) - Yang, Danqin; Lu, Zihao; Qi, Xiaoqing; Yan, Dandan; Gao, Qinwei; Zhan, Da; Jiang, Yuan; Liu, Xiang Yang
Abstract : Correction for 'Fabrication of a uniaxial cellulose nanocrystal thin film for coassembly of single-walled carbon nanotubes' by Danqin Yang et al., RSC Adv., 2016, 6, 39396–39400.